2020
DOI: 10.1016/j.jvs.2019.04.488
|View full text |Cite
|
Sign up to set email alerts
|

Review of serum biomarkers in carotid atherosclerosis

Abstract: Background: Carotid artery atherosclerotic stenosis is a preventable major cause of stroke, but there is still a need for definition of high-risk plaque in asymptomatic patients who might benefit from interventional therapies. Several image markers are recommended to characterize unstable plaques. The measurement of serum biomarkers is a promising method to assist in decision making, but the lack of robust evidence in the carotid environment burdens their potential as a standard of care. The goal of this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 124 publications
0
69
0
Order By: Relevance
“…1A). Impaired regulation of the HM cycle results in elevated levels of Hcy, a human disease termed as hyperhomocysteinemia (HHcy), an established independent risk factor for cardiovascular disease (CVD), stroke, type II diabetes, osteoporosis and dementia [[1], [2], [3]].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…1A). Impaired regulation of the HM cycle results in elevated levels of Hcy, a human disease termed as hyperhomocysteinemia (HHcy), an established independent risk factor for cardiovascular disease (CVD), stroke, type II diabetes, osteoporosis and dementia [[1], [2], [3]].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focused on inflammatory markers within the atherosclerotic plaque and revealed distinct cytokine signatures associated with plaque vulnerability 13 . Likewise, numerous studies investigated circulating biomarkers regarding presence of carotid stenosis or measures of cerebrovascular risk 14 www.nature.com/scientificreports/ local plaque inflammation 15,16 or rather an atherothrombotic event leading to cerebrovascular symptoms. To answer this question, we chose a comprehensive approach in order to identify a systemic cytokine pattern that is associated with characteristics of vulnerability or with the occurrence of ischaemic cerebrovascular events in carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory factor (eg. IL-6), lipid, MMP-9, adiponectin, neutrophil count and total bilirubin have the potentials to improve the plaque de nition in complications, thereby choosing asymptomatic patients for the interventional therapies [19]. IL-6 is a proin ammatory cytokine that has a role in the development of atherosclerotic plaque, and miR-126 mimic has been found to degrade the secretion of in ammatory cytokines [20].…”
Section: Discussionmentioning
confidence: 99%